2010
DOI: 10.1021/jf1009395
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Fertilizer Use via Controlled Release of a Bacteria-Encapsulated Film Bag

Abstract: A phosphate-solubilizing bacterium ( Burkholderia cepacia isolate) encapsulated in maleic anhydride (MA) grafted onto poly(butylene succinate adipate) (PBSA) and then combined with starch as film bag material (PBSA-g-MA/starch) incubated in a saline solution required approximately 20 days to deplete the starch in the film bags. Thereafter, the cell concentration in the saline solution increased significantly because of the release of cells from the severely destroyed film bags and also their growth by use of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It has recently been demonstrated that the biodegradation of PBAT under mesophilic conditions is a slow process, taking many months, and higher levels of mineralization are difficult to achieve. ,, For example, in the work by Rychter et al, 15% weight loss was recorded after 10 months of incubation at 30 °C . Developing PBAT-based materials with improved biodegradation under mesophilic conditions in soil would help to achieve decomposition of disused films, e.g., mulching films, in situ , and, hence, decrease expenses connected with collecting and composting of the material. ,, Another advantage could be an eventual positive effect on crops and soil structure or the possibility of incorporating fertilizers or plant protection agents. , …”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that the biodegradation of PBAT under mesophilic conditions is a slow process, taking many months, and higher levels of mineralization are difficult to achieve. ,, For example, in the work by Rychter et al, 15% weight loss was recorded after 10 months of incubation at 30 °C . Developing PBAT-based materials with improved biodegradation under mesophilic conditions in soil would help to achieve decomposition of disused films, e.g., mulching films, in situ , and, hence, decrease expenses connected with collecting and composting of the material. ,, Another advantage could be an eventual positive effect on crops and soil structure or the possibility of incorporating fertilizers or plant protection agents. , …”
Section: Introductionmentioning
confidence: 99%
“…This material was shown to be biodegradable in biodegradation tests carried out on thin polymer films (60 × 60 × 0.5 mm) under controlled conditions at 50 °C for 3 months in a mixture of sand and compost, according to the previously reported procedure . The weight losses of the PBS/DLA copolyester were approximately 5 wt % after 1 month, 8 wt % after 2 months, and 10 wt % within 3 months of incubation; however, there are reports on complete biodegradation of PBS and PBS blends with various organic materials. ,, …”
Section: Methodsmentioning
confidence: 93%
“…26 The weight losses of the PBS/DLA copolyester were approximately 5 wt % after 1 month, 8 wt % after 2 months, and 10 wt % within 3 months of incubation; 25 however, there are reports on complete biodegradation of PBS and PBS blends with various organic materials. 22,23,27 Despite the fact that the use of PBS/DLA in the preparation of controlled-release fertilizers may bring many benefits, especially in the context of environment protection, it should be kept in mind that PBS is not a cost-effective material. The price of commercially available PBS is approximately 5.4−5.6 euro/kg, and it is comparable with other synthetic biodegradable polyesters 28 but slightly higher than the price of biobased, biodegradable polymers from natural resources and several times higher than the price of conventional, not biodegradable synthetic polymers.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizers have been used to supply nutrients in growing media for many years, and they are added to soil to supply one or more plant nutrients essential to the growth of plants. , However, the nutrients of a common fertilizer is lost to the environment easily and cannot be abundantly taken up by plants, which results in the contamination of water, air, etc . An effective way to improve nutrient use efficiency while reducing the environmental hazards is using slow- or controlled-release fertilizers (SCRFs), contributing to the sustainable development of agriculture and the environment. In comparison to traditional fertilizers, SCRFs have many advantages.…”
Section: Introductionmentioning
confidence: 99%